Perancangan Interior Jill Stuart Fashion and Beauty Platform di Surabaya - Verina Benita Santoso; mariana wibowo; dody wondo (Intra, 2013)
Jill Stuart Fashion and Beauty Platform in Surabaya is designed to meet the needs of market demand which appears because of Korean Wave Style which also came to make a big influence in Indonesia. The main facilities at this platform consist of lobby, retail, café, and fashion show runway area. The concept which is used in its Interior is “Pulchritude”, a word that describes something that is pretty, gorgeous and charming, and supported by modern American colonial style as Jill Stuart is a brand which is based in New York. Shabby Chic Style accessories is also added to enhance the space feeling to be like Jill Stuart’s brand image “innocent, pretty, cute and sexy”. The design result which is presented in Jill Stuart Fashion and Beauty Platform are cozy, chic and classy, so the visitors would enjoy the one-stop shopping service in accordance with Jill Stuart’s motto.